2006
DOI: 10.1096/fj.06-5718com
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulators of ribosomal biogenesis are increased in the unloaded heart

Abstract: Mechanical unloading of the rat heart increases both protein synthesis and protein degradation. The transcriptional mechanism underlying increased protein synthesis during atrophic remodeling is not known. The aim of this study was to identify transcriptional regulators and the gene expression profile regulating protein synthesis in the unloaded rat heart and in the unloaded failing human heart. We measured DNA binding activity, transcript levels, and protein expression of transcriptional regulators of protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…Because Akt is not activated in the heterotopically transplanted rat heart, mTOR must be activated by Akt independent pathways in this model of cardiac atrophy 41 . Also consistent with the increase in protein synthesis in the unloaded rat heart is the increase of transcriptional regulators of ribosomal biogenesis and the activation of a hypertrophic gene program 43 . We have therefore proposed, that atrophic remodeling of the unloaded heart activates both protein synthesis and degradation 44 .…”
Section: Protein Turnover In Cardiac Atrophymentioning
confidence: 74%
“…Because Akt is not activated in the heterotopically transplanted rat heart, mTOR must be activated by Akt independent pathways in this model of cardiac atrophy 41 . Also consistent with the increase in protein synthesis in the unloaded rat heart is the increase of transcriptional regulators of ribosomal biogenesis and the activation of a hypertrophic gene program 43 . We have therefore proposed, that atrophic remodeling of the unloaded heart activates both protein synthesis and degradation 44 .…”
Section: Protein Turnover In Cardiac Atrophymentioning
confidence: 74%
“…It is possible these genes alter cardiac protein synthesis via rRNA processing. Although no definitive link between rRNA processing and heart development has been reported, increased MYC and rRNA have been shown in human hearts after mechanical unloading [82]. The enrichment of genes related to rRNA processing in candidate CNVs warrants further investigation.…”
Section: Resultsmentioning
confidence: 99%
“…About 80–85% of the cellular RNA is ribosomal, and in human and rat heart muscle it has been shown that the rRNA content reflects the number of ribosomes (Millward et al 1973; Razeghi et al 2006). Assuming that the stability of mRNA, ribosomes and polysomes are similar in high and low oxidative fibers, the higher total RNA content in the rat high oxidative soleus muscle compared to the low oxidative EDL (Fig.…”
Section: Fiber Type-related Differences In the Machinery For Protein mentioning
confidence: 99%